Optimization of Plant Growth and Yield Through Innovation of the Verticultural Materials and Media - Sitawati Sitawati; Agus Suryanto; Euis Elih Nurlaelih (Research Journal of Life Science, 2016)
Vertikultur is one of effort to agricultural of narrow as urban farming. Efforts to obtain plant container and plant medium on vegetables pakcoy to compare the productivity model of vertical planting and horizontally with the application of fertilizer on strawberry plants optimally. The first study aimed to determine the combination of growing medium and materials vertikultur which efficient and effective for pakchoy growth in vertikultur, then continued a second study that application of a combination of materials vertikultur and fertilizer N, P and K on the strawberry plants at planting vertical and horizontal models. Combination treatment is the first study consisted of the first factor is the material vertikultur form of carpet, gunny sacks and plastic, while the second factor is the growing media consisting of soil, humus, rice husk and cocopeat using a randomized design factorial with three replications conducted in Gresik, East Java. In the research into two, the first factor is a model of planting both horizontally and vertically, while the factor two is a dose of NPK (0%, 25%, 50%, 75% and 100%) on strawberry plants by using Design Grid Divided by 3 replications implemented in Batu, East Java. The results showed that the material vertikultur carpets and plastic with humus media have fresh weight pachoy same plant with soil media. Average penamaman with vertical and horizontal models have the same weight of strawberries where urea 3.75 g / tan, SP36 5g / tan and KCl 5 g / tan increase the yield per plant.